Civil claim in criminal proceedings: conceptual approaches to understanding essence - Moseiko, Stanislav (Archives of Criminology and Forensic Sciences, 2024)
The article is devoted to the issue of compensation for damage caused by a criminal offense by filing a civil claim in criminal proceedings, which is relevant for modern science of criminal procedure. The author draws attention to the fact that fundamental changes in the current criminal procedural and civil legislation necessitate a revision of established approaches not only to the procedural procedure for filing and considering a civil claim in criminal proceedings, but to doctrinal approaches to understanding the essence of the institution of a civil claim, because a typical mistake in scientific research is the use of established legal “clichés” in understanding modern institutions, including the institution of a civil claim in criminal proceedings. Thus, the purpose of the article is to understand the essence of the conceptual changes that have occurred in the regulatory regulation of the institution of a civil claim in criminal proceedings, as a fundamental concept of the doctrinal understanding of the form of considering a civil claim. The author’s approaches are based on general and special methods of scientific research. The logical method was used to examine the concept of “joint process”; the systemic method was used to understand the problem in its comprehensive vision and to form conclusions; the hermeneutic method was useful for interpreting the norms of criminal procedural law. According to the results of the study, a conclusion was made about the inexpediency of understanding a civil claim in criminal proceedings as a joint process, since it cannot be considered as a combination of criminal proceedings and proceedings regarding a civil claim in one proceeding. The procedure for compensation for damage on the basis of a declared civil claim operates within the framework of criminal procedural legal relations, the norms of civil procedural law are auxiliary, as indicated by Part 5 of Article 128 of Criminal Procedural Code of Ukraine, and therefore it is a single process devoid of contradictions between the two branches of law.